Replacement of frozen fish meat based diet with artificial diets in rearing of coral trout Plectropomus leopardus (Lacepede, 1802) fingerlings - Ma, Zhenhua; Zhang, Nan; Guo, Huayang; Zheng, Panlong; Zhang, Dianchang (Indian Journal of Fisheries, 2015)
This study compared the efficacy of four diets in rearing of coral trout Plectropomus leopardus during the nursery phase. Details of the experimental diets used in the study are: Diet 1 - prepared with a mixture of golden pompano meat and shrimp meat (2:1, w:w); Diet 2 - prepared with golden pompano meat, shrimp meat, and fish meal (2:1:3, w:w:w); Diet 3 - a commercial pellet with 46% protein (Hairui®, P. R. China) and Diet 4: a commercial pellet with 53% protein (Huacheng®, P. R. China). Fish fed Diet 2 showed the lowest survival rate. The specific growth rate (SGR) of fish fed with Diet 3 and Diet 4 were significantly higher than those fed with Diet 1 and Diet 2 (p< 0.05). Food conversion rates (FCR) of fish fed with Diet 3 (1.5 ±0.4) and Diet 4 (2.0 ±0.3) were significantly lower than those fed with Diet 1 (5.5 ± 0.6) and Diet 2 (7.7 ± 1.7, p< 0.05). Results from the present study demonstrated that it is feasible to feed coral trout fingerlings with commercial pellets during nursery phase. The fish meat based diet can be replaced with Diet 3 or Diet 4, and among these the most economic diet was Diet 3 with the production cost rate of CN ¥ 0.02 per g biomass.